Bridging gaps in Malaysian acne vulgaris guidelines: advisory statements on trifarotene for facial and truncal acne - Mohd Affandi, Azura; Ch'ng, Peter Wee Beng; Teoh, Benji Tze Yuen; Yap, Evelyn Wen Yee; Ch'ng, Chin Chwen; Foo, Seow Hoong; How, Kang Nien; Kwan, Zhenli; Tang, Jyh Jong; Tan, Wooi Chiang; Kon, Khen; Poh, Wei Thian (John Wiley and Sons Inc, 2025)
Background: Trifarotene, a fourth-generation topical retinoid, offers a novel therapeutic option for facial and truncal acne. However, its role was only briefly addressed in Malaysia's 2022 Clinical Practice Guidelines (CPGs) due to its unavailability at the time. This paper aims to provide expert advisory statements on the integration of trifarotene into acne management in Malaysia, addressing evidence gaps in guideline coverage, particularly for truncal acne and acne-induced sequelae. Methods: A literature review was conducted to synthesize evidence on trifarotene's efficacy, safety, and clinical positioning. An advisory panel of 10 Malaysian dermatologists reviewed the evidence and provided consensus through structured surveys and discussion meetings. Three illustrative case studies were included to demonstrate the real-world application of trifarotene. Results: Ten advisory statements were finalized, addressing trifarotene's role in acne algorithms, patient selection, dosing strategies, combination therapy, and management of acne sequelae. Evidence supports its use for both facial and truncal acne, with additional benefits in acne-induced hyperpigmentation and atrophic scarring. The panel recommended practical approaches to optimize tolerability and adherence, such as the CTMP (Cleanse-Treat-Moisturize-Photoprotect) regimen and incremental application strategies. Real-world cases demonstrated trifarotene's utility in diverse clinical settings. Conclusion: These advisory statements provide clinical guidance on the use of trifarotene in Malaysia and support its integration into routine acne management. As current CPGs may remain unchanged in the near term, these recommendations aim to inform evidence-based practice while bridging gaps in local dermatologic care.